Bioethanol production potential of a novel thermophilic isolate Thermoanaerobacter sp. DBT-IOC-X2 isolated from Chumathang hot spring. (September 2018) - Singh, Nisha; Puri, Munish; Tuli, Deepak K.; Gupta, Ravi P.; Barrow, Colin J.; Mathur, Anshu S.
Abstract: Dilute acid pretreatment of biomass generates enormous amount of hydrolysate (rich in inhibitors and pentose sugars), that remains unutilized for bioethanol production due to inadequacy of efficient C5 -fermenting organisms. In this study, a predominantly pentose fermenting extremely thermophilic bacterium strain DBT-IOC-X2, pertaining to the genus Thermoanaerobacter was isolated from Himalayan hot spring. Batch experiments indicated substantial inhibitor resistance (2 g dm −3 for furfural, 5-HMF, and acetic acid), substrate tolerance (∼15 g dm −3 ), co-sugar fermentation ability (co-production ethanol yield of 0.29 g/g), and high ethanol yield (83.57% and 91.12% of the theoretical maximum from 5 g dm −3 glucose and xylose, respectively) by the bacterium at 70 °C and pH 8.0. Here, bioethanol production process was developed using pre-treated rice straw hydrolysate (PRSH) as low-cost agro-waste and 83.47% of the total sugar conversion was obtained. This study shows that Thermoanaerobacter sp. DBT-IOC-X2 could utilize diluted PRSH efficiently to improve the overall cost-effectiveness of biomass processing to bioethanol. Graphical abstract: Image 1 Highlights: Novel C5 -fermenting thermophilic anaerobic bacteria isolate, Thermoanaerobacter sp. DBT-IOC-X2, from Chumathang hot spring. Applicability of hemicellulose and inhibitor rich waste stream for cost effective ethanol production. Higher ethanol yield of 83.57% and 91.12% of the theoretical maximum from glucose and xylose, respectively. Co-sugar fermentation ability.